PERFIL DOS PROCESSOS POR ERRO MÉDICO NA PROMOTORIA DE JUSTIÇA ESPECIALIZADA DE DEFESA DA SAÚDE EM SÃO LUÍS NO PERÍODO DE 2002 A 2007 - Maia, Deíla Barbosa (2008)
Objective: to characterize the profile of the criminal lawsuits regarding medical malpractice initiated by the Health Defense Public Prosecutor's office in São Luís, capital of the Brazilian State of Maranhão, between 2002 and 2007. Methodology: the research was initiated through a retrospective study in the archive of the Public Prosecutor's office by fulfilling files with the lawsuits data. The data found was then compared with information from other places in Brazil and the world. Results: 43 processes, involving a total of 47 patients, were analyzed, Most of the victims were females (63.8%), with average age of 34 years old and living in São Luís (91.5%). The denouncers were relatives (46.5%) or the victims themselves (34.9%). The most common accusation was of non-intentional injury (51.1%), followed by involuntary manslaughter (37.8%), being negligence the kind of culpability in most cases (49%). In 93% of the lawsuits the medical chart was attached. The majority of the lawsuits had not been ruled yet (86%). 66 medical doctors were accused. In 65.1% of the cases only one doctor was involved, most of them were males (54.5%), with average age of 41 years old and specialized in gynecology and obstetrics (31.8%), followed by pediatrics (10.6%) and general surgery (7.6%). Regarding their education, the majority (91%) graduated in medicine in public universities. It was not possible to check whether or not they had some kind of post-graduation studies. Most of the cases were linked to urgency/emergency (69.8%) and surgeries (60.5%), occurred in public institutions (58.1%), considered as general hospitals (41.8%), and paid by the government (83.7%). Conclusion: The processes analysed were denounced mainly by relatives of the patients and most of victims were females. The most common accusation was of non-intentional injury, by negligence. The majority of the lawsuits had not been ruled yet. The medical doctors envolved were males, with average age of 41 years old, specialized in gynecology and obstetrics and graduated in medicine in public universities. The attendances related to the processes have occurred in urgency/emergency situations, %), in public institutions and paid by the government.